Realidad e inversión en el alumno en el Perú - Cano Rojas, María Elizabeth (2010)
The student's current situationin Peru is very critica! since there are several factors that irtipede their development, specially the conditions under which they live, and the social, economic and health aspects that prevent them from studying. Likewise, the reality of education is shown in this article: how it is financed, the inequity in the different sectors, the educational gap regarding the conditions and infrastructure, the condition under which students learn and teachers teach. This is only a glimpse on how we are now, and how we will be consideringthat today students are our future. Thus, if there is nota good education from the beginning, little will hold the future for us.